The 20-20-20 Rule: An Initiative to Maintain Children's Eye Health Amidst the Widespread Use of Gadgets - Windi Indria Rini; RA. Hani Faradis; Dewi Masithah; Rafifah Muthi Al-Khansa; Nurul Hidayatih; Andrew Adhitya Pratama Sunaryo (UKInstitute, 2026)
The widespread use of gadgets among children, including santri (Islamic boarding school students), contributes significantly to ocular health issues such as eye strain, dry eyes, and escalating myopia rates. Recognizing the limited awareness of excessive screen exposure risks, this community service intervention aimed to improve the knowledge and awareness of 38 Santri Husada (Student Health Cadres) at Assalafi Al-Fithrah Islamic Boarding School in Surabaya by implementing The 20-20-20 Rule. The methodology employed an interactive educational approach divided into three phases: preparation, implementation, and evaluation. The core procedure involved pre-test administration, interactive health sessions, practical simulation of the 20-20-20 Rule, educational leaflet distribution, and a post-test. Data were analyzed using the N-Gain score to measure effectiveness. Results demonstrated a significant knowledge improvement, with the average score increasing from 5.8 (pre-test) to 8.8 (post-test). N-Gain analysis indicated that 71.05% of participants achieved a high-improvement category, confirming the effectiveness of the interactive educational method. This activity successfully enhanced the santri's health understanding and is deemed a potential sustainable health education model for boarding schools, although long-term monitoring is recommended.